2017
DOI: 10.22219/jie.v1i3.6154
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Peningkatan Ekonomi Masyarakat Di Agrowisata Belimbing Karangsari Kota Blitar

Abstract: Kelurahan Karangsari after established of Karangsari Starfruit Agrotourism in Blitar City we can see economic development in society with how Starfruit farmer’s income transformed. For knowing income differentiation of Starfruit farmer we use paired sample t-test method. This research found that after established of Karangsari Starfruit Agrotourism in Blitar City give positive influence for Starfruit farmer. The influence is the increasing demand for the product, the creation of product quantity, the creation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Increased harvest area, competitive productivity, and profitable business will mean that star fruit commodities will be able to be produced continuously in the future. Agrotourism can also be an opportunity to increase product demand, production quantities, and selling prices, develop product processing innovations, and open up employment opportunities for the community ( [29].…”
Section: Continuity Of Vegetable and Fruit Crops Production In Brebes...mentioning
confidence: 99%
“…Increased harvest area, competitive productivity, and profitable business will mean that star fruit commodities will be able to be produced continuously in the future. Agrotourism can also be an opportunity to increase product demand, production quantities, and selling prices, develop product processing innovations, and open up employment opportunities for the community ( [29].…”
Section: Continuity Of Vegetable and Fruit Crops Production In Brebes...mentioning
confidence: 99%
“…The benefits for agricultural businesses by developing agro-tourism diversification vary. [7] examined the impact of starfruit Agro-tourism in Karangsari, Blitar City, and found that agro-tourism had a positive impact on star fruit farmers' businesses. These positive impacts include increasing the The Agro-tourism is defined as an agricultural tourism that provides entertainment and education in various series of activities related to agricultural and pleasure [16].…”
mentioning
confidence: 99%
“…Adanya Agrowisata Belimbing Karangsari berdampak baik karena dapat menopang perekonomian warga sekitar melalui mata pencaharian sebagai penjual buah belimbing, oleh-oleh produk olahan belimbing dan pegawai di Agrowisata. Menurut (Aida et al, 2017), sejak berdirinya Agrowisata Belimbing Karangsari, terjadi peningkatan permintaan buah belimbing dan produk olahan setiap minggunya. Kenaikan permintaan tersebut menjadi bukti bahwa adanya dampak positif pada perekonomian masyarakat sekitar.…”
unclassified